"Clicked" galactosyl anthraquinone on graphene electrodes for the label-free impedance detection of live cancer cells. (October 2015) - Cui, Lei; Zhu, Bi-Wen; Qu, Song; He, Xiao-Peng; Chen, Guo-Rong
Abstract: Detection of live cells has been difficult with conventional biochemical techniques that require the lysis of cells to release a biomarker. This study describes the simple construction of a galactosyl anthraquinone dye for the label-free impedance detection of live cancer cells. A click dipolar reaction of an alkynyl anthraquinone with azido galactoside yields the anthraquinone probe which can be subsequently employed to bind to a graphene-coated screen printed electrode by self-assembly. By taking advantage of selective sugar-receptor recognitions, live cancer cells without being labeled, can be captured by the electrode, producing a sensitive impedance signal. Knockdown of the receptor leads to a sharp decrease of the impedance signal, suggesting the suitability of the electrode system for the direct live cell capture based on ligand-receptor recognitions. Graphical abstract: Highlights: Anthraquinonyl galactoside (AG) was synthesized by CuAAC. AG could self-assemble to a graphene electrode for impedance detection of lectins. AG@graphene electrode could probe receptor-rich cancer cells in a label-free manner. Knockdown of the receptor led to decreased detection signal.